Charlie Chan in London [videorecording (DVD)] - Forde, Eugene, 1898-1986; Oland, Warner, 1880-1938; Leyton, Drue; Milland, Ray; Barrie, Mona, 1909-1964; Mowbray, Alan, 1896-1969; Kinnell, Murray, 1889-1954; Biggers, Earl Derr, 1884-1933 (20th Century Fox Home Entertainment, 2006)
"To investigate a young woman's claim that her brother has been framed for murder, Chan invites himself to a stately English manor, where guests gathering for a fox hunt unwittingly harbor the real killer!" -- Container.